Students Consumptive Behavior and Its Implications for Achieving SDGs - Putri Wahyu Ningsih; Dhiah Fitrayati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to analyze the influence of financial literacy and digital literacy on consumptive behavior with the use of digital payments as a mediating variable. The research was conducted among students of the Economic Education program from the 2021, 2022, and 2023 class. Method: This research uses a quantitative method with a causal associative research type. The data analysis technique in this study uses the Structural Equation Modeling (SEM) analysis method with the Partial Least Squares (PLS) approach in SmartPLS 4 software. Results: The results show that financial literacy has a negative effect on consumptive behavior, digital literacy has a negative effect on consumptive behavior, financial literacy negatively affects the use of digital payments, and digital literacy positively affects the use of digital payments. Furthermore, the use of digital payments positively influences consumptive behavior. Financial literacy also negatively affects consumptive behavior through the use of digital payments, while digital literacy positively affects consumptive behavior through the use of digital payments. Novelty: This study simultaneous applies the Theory of Planned Behavior (TPB) and the Unified Theory of Acceptance and Use of Technology (UTAUT) to analyze student’ consumptive behavior, with the use of digital payment as a mediating variable between financial literacy and digital literacy.